Therapeutic Dressings and Wound Healing Applications 2020
DOI: 10.1002/9781119433316.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mixed Infections in Wounds

Abstract: 2.1 Background 2.2 Aetiology of Diabetic Foot Ulcers 2.3 Standard of Care for Treatment of Diabetic Foot Ulcers 2.4 Commonly Used Wound Dressings for Diabetic Foot Ulcers and Their Mechanism of Action 2.5 Absorbent and Superabsorbent Dressings 2.6 Alginates 2.7 Films 2.8 Foams 2.9 Honeys 2.10 Hydrogels 2.11 The Role of a Split Thickness Skin Graft in Diabetic Foot Ulcers 2.12 Negative Pressure Wound Therapy 2.13 Larval Therapy 2.14 Clinical Case Studies from Multidisciplinary Diabetic Foot Clinic 2.14.1 Neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 114 publications
0
4
0
1
Order By: Relevance
“…Mixed bacterial-fungal (polymicrobial) infection is one of the most common complications of diabetic foot ulcers (DFUs). Bacteria and fungi work synergistically or antagonistically to promote survival of the species within a host-specific niche (Ahmed & Boateng, 2020;Dhamgaye et al, 2016). Patients with DFUs lack sensation (neuropathy) due to poor blood circulation in the foot area, which makes them unaware of deteriorating infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed bacterial-fungal (polymicrobial) infection is one of the most common complications of diabetic foot ulcers (DFUs). Bacteria and fungi work synergistically or antagonistically to promote survival of the species within a host-specific niche (Ahmed & Boateng, 2020;Dhamgaye et al, 2016). Patients with DFUs lack sensation (neuropathy) due to poor blood circulation in the foot area, which makes them unaware of deteriorating infections.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of mixed infection in DFUs suggest that the treatment outcomes are very poor. Various studies have reported that several approaches such as cleansing followed by debridement, hyperbaric oxygen therapy, phage therapy and antimicrobial administration have been employed to prevent and control diabetic foot infections (Ahmed & Boateng, 2020;Peters et al, 2012). In the case of antimicrobial therapy, systemic administration (oral or parenteral) of high doses of antibiotics is prescribed to achieve adequate blood serum concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, topical antimicrobial treatments require intensive and painful dressing changes and can impair wound healing by depositing toxic antimicrobial concentrations at the site of infection. [ 79 , 80 ] Due to the intense selective pressure associated with the use of high antibiotic doses at the injury site and the requirement for long treatment regimens, [ 81 , 82 , 83 , 84 , 85 , 86 ] burn wounds are also potential sites for the emergence and propagation of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Wound dressings can be produced from a variety of materials including starch, dextran, chitosan, alginate, polyurethane, cellulose derivatives, hyaluronic acid, polysaccharide derivatives, collagen and gelatin [13,14]. Based on the production method and materials used, modern wound dressings can be classified into several categories: films, foams, nonwovens (including electrospun and blow spun), 3D printed dressings, and hydrogels [15].…”
Section: Wound Dressingsmentioning
confidence: 99%